The Effectiveness Of Slow Release Potassium Fertilizer Found On The Productivity Of Oil Palm (Elaeis guineensis Jacq.) That Have Produced In Peatland - Ardian Ardian; Ugei Ramahendra Al-Faith; M. Amrul Khoiri; Nurbaiti Nurbaiti; Angga Pramana (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
Oil palm (Elaeis guineensis Jacq.) comes from the Palmae family which is a source of vegetable oil. The production of oil palm plants that continues to increase certainly needs efforts, one of which is through fertilization. This study aimed to see the effectiveness of the frequency of treatment with slow release potassium fertilizer on the productivity of oil palm (Elaeis guineensis Jacq.) plants that have produced on peatlands. This has been implemented in an oil palm plantation in Pangkalan Baru Village, Siak Hulu District, Kampar Regency. The research has been carried out for six months starting from February 2021 to July 2021. This research was conducted using a non-factorial Randomized Block Design (RAK). The treatment consisted of 4 levels of treatment, namely a dose of 3 kg given 1 time / 6 months, a dose of 3 kg given 1.5 times / 6 months, a dose of 3 kg given 2 times / 6 months, and a dose of 3 kg given 3 times / 6 months. Each treatment was repeated 5 times. Therefore, 20 experimental units were obtained. Each experimental unit consisted of 3 sample plants so that the total number of sample plants used was 60 plants. The observed parameters were the number of female flower bunches, the number of male flower bunches, sex ratio, number of bunches, bunch weight, fresh fruit weight, and fresh fruit volume. The results of the research that have been carried out show that the application of treatment with a dose of 3 kg given 1.5 times / 6 months significantly increases the weight of bunches, weight of fresh fruit, and volume of fresh fruit on mature oil palm plantations on peatlands.